Intercropping and Rhizobium Inoculation Affected Microclimate and Performance of Common Bean (Phaseolus vulgaris L.) Varieties - Shemeles Tesfaye Shumet; Tewodros Ayalew; Amsalu Gobena Roro; Hussien Mohammed Beshir (Scientifica)
A field experiment was carried out at Hawassa, during the 2020 cropping season with the objective to evaluate the impact of maize-common bean intercropping and Rhizobium inoculation on microclimate, growth, and yield of common bean varieties. Treatments consisting of two common bean varieties, two levels of inoculation and three spatial arrangements of common bean with another sole maize were laid out in a factorial arrangement in a randomized complete block design (RCBD) with three replications. The results revealed that the main effect of spatial arrangements highly significantly (P < 0.001) affected soil and leaf temperature. Soil moisture content was improved under intercropped plots compared with sole cropping. The intensity of light and qualities, such as red, far-red, and photosynthetically active radiations (μmol m−2 s−1) and ultraviolet rays (UV)-A, UV-B (W m−2), were reduced under intercropping as compared to the sole. Interaction effects of variety, spatial arrangements, and inoculation significantly (P < 0.01) affected plant height and leaf area index. Inoculated sole Nassir outperformed for plant height and leaf area index. Inoculated sole Hawassa Dume variety performed best for nodule number plant−1, nodule dry weight plant−1, pods number plant−1, 100 seed weight, grain yield, and above-ground biomass yield. The highest grain yield (2.8 t ha−1) was recorded from inoculated sole Hawassa Dume. However, considering the equivalent ratio (LER), intercropping with one maize row to two haricot bean rows spatial arrangements was productive by 62% more than sole cropping (total land equivalent ratio of 1.62%).